The Feasibility and Suitability of Jobsheet-Assisted Modules Developed Using the 4D Model for Fashion Business Learning - Hanim, Halida; Rahma Dewi, Eka; Anggraini, Yudhistira (Jurnal PAJAR (Pendidikan dan Pengajaran), 2025)
Learning in the fashion business field requires considerable time and effort because it combines theoretical concepts of business management with practical sewing procedures. These complex learning activities often make it difficult for students to fully comprehend and apply the material effectively. This study aimed to determine the feasibility and suitability of a jobsheet-assisted module developed using the 4D (Define, Design, Develop, Disseminate) model for Fashion Business learning. The research employed a research and development (R&D) method following the 4D stages. The feasibility of the developed module was validated by material experts (87.7%), media experts (93.8%), and students through small, medium, and large group trials. The small group trial involving 10 students achieved 88.25%, the medium group trial with 25 students reached 91.8%, and the large group trial involving 37 students achieved 96.4%, all of which fall into the very suitable category. These results indicate that the jobsheet-assisted module is feasible and suitable for use as a learning medium in Fashion Business courses, providing an integrated approach that connects management concepts with hands-on sewing practice.